2021
DOI: 10.3389/fcell.2021.738786
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Phototoxicity in a Mammalian Cell Line: How Low Levels of Blue Light Affect Motility in PC3 Cells

Abstract: Phototoxicity is a significant constraint for live cell fluorescence microscopy. Excessive excitation light intensities change the homeostasis of the observed cells. Erroneous and misleading conclusions may be the problematic consequence of observing such light-induced pathophysiology. In this study, we assess the effect of blue light, as commonly used for GFP and YFP excitation, on a motile mammalian cell line. Tracking PC3 cells at different light doses and intensities, we show how motility can be used to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Finally, Figure 4F shows the interdivision times determined from the different models and from the fluorescence data. We make three observations based on these results: (1) the results from the high-density model most closely matches the GFP fluorescence reference dataset, (2) we track more cells from division to division with models developed from data with high cell densities, and (3) the low-density 2D U-Net results in interdivision times less than 9.5 hours – the lower limit of biologically realistic interdivision times (21). This result suggests that using the low-density 2D U-Net leads to more tracking errors than the high density 2D U-Nets.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, Figure 4F shows the interdivision times determined from the different models and from the fluorescence data. We make three observations based on these results: (1) the results from the high-density model most closely matches the GFP fluorescence reference dataset, (2) we track more cells from division to division with models developed from data with high cell densities, and (3) the low-density 2D U-Net results in interdivision times less than 9.5 hours – the lower limit of biologically realistic interdivision times (21). This result suggests that using the low-density 2D U-Net leads to more tracking errors than the high density 2D U-Nets.…”
Section: Resultsmentioning
confidence: 82%
“…We assessed track lengths as an estimate of the quality of our cell tracking workflow. We quantified cell-tracking accuracy with three different measurements: (1) the linkage error rate per track, (2) the track length distribution and (3) the interdivision times. Using the GFP fluorescence to generate reference tracks, the data in Figure 4C show the linkage error rate computed for an entire dataset (4000 initial cells) to be approximately 0.005 on average, which corresponds to one potential linkage error every 8 hours on average over the course of a single track.…”
Section: Resultsmentioning
confidence: 99%
“…The noncommutativity not only is attributed to the complex conformational dynamics and allostery within protein structures but also is affected by the input signals, such as the concentration of rapamycin, the blue light intensity, and the illumination time. A high dose of rapamycin can affect cell motility and strong blue light can cause phototoxicity and damage the cells (78)(79)(80). On the other hand, weak input signals cannot successfully activate or inactivate the target protein.…”
Section: Discussionmentioning
confidence: 99%
“…29−32 Besides, short wavelength excitation is regarded as phototoxicity to cells; hence, CDs with blue or green emission generally excited by short wavelength light are unfavorable in cell labeling. 33,34 Therefore, developing intrinsic mitochondria-targeted CDs with long-wavelength excitation, high stability, and excellent mitochondrial affinity for in situ monitoring of mitochondrial dynamics is highly desirable.…”
mentioning
confidence: 99%
“…Carbon dots (CDs), as promising fluorescent nanomaterials with good biocompatibility, excellent cell permeability, bright fluorescence, high photostability, and simple synthetic routes, have become attractive candidates for bioimaging. , In addition, some studies have demonstrated that surface functional groups of CDs may decide the special targeting ability to diverse organelles, such as p -phenylenediamine and 4-carboxybutyl triphenylphosphonium-modified cationic CDs for nuclear targeting, morpholine-functionalized CDs for lysosome targeting, lauryl amine-modified CDs for endoplasmic reticulum targeting, l -cysteine-rich chiral CDs for Golgi apparatus targeting, 2-dimethylamino-5-fluorobenzimidazole fluorophore-based amphiphilic CDs for LD targeting, and lipophilicity and surface group-mediated tunable organelle imaging. With regard to reported mitochondria-targeting CDs, their targeting ability is usually attributed to the triphenylphosphonium moiety, which is toxic to cells and requires additional post-modification steps for staining. Recently, CDs with intrinsic mitochondrial targeting capability depending on the positive charge and related surface functional groups (such as the lipophilic cation of rhodamine) have been reported; however, the studies on mitochondrial dynamics tracking have been little reported. , Nevertheless, there has been some literature about stimulated emission depletion microscopy and stochastic optical reconstruction microscopy methods for mitochondrial dynamics imaging, which need specific organic molecular probes to label cells. Besides, short wavelength excitation is regarded as phototoxicity to cells; hence, CDs with blue or green emission generally excited by short wavelength light are unfavorable in cell labeling. , Therefore, developing intrinsic mitochondria-targeted CDs with long-wavelength excitation, high stability, and excellent mitochondrial affinity for in situ monitoring of mitochondrial dynamics is highly desirable.…”
mentioning
confidence: 99%